The influence of the wind structure definition in the standard k-ε model of turbulence on the distribution of pressure coefficient on the façades of the prism - Jamińska, Paulina (Budownictwo i Architektura / Civil and Architectural Engineering, 2012)
The paper deals with the influence of the definition of turbulence kinetic energy k and dissipation of turbulence kinetic energy ε on wind pressure coefficient distribution on walls of rectangular model. The investigation includes computer simulations for the four cases of boundary conditions, the most common in the literature. In some analysed cases, the wind structure characteristics used in computations were derived from experimental studies performed in the wind tunnel. The results in the form of pressure coefficients were analyzed on the basis of their relevance to the use in the field of wind engineering. All calculations were performed in ANSYS FLUENT with use of standard k-ε model. The 3D model of the flow around the prism was considered in calculations.